STUDENTS’ LEARNING STYLE: A CASE STUDY OF SENIOR HIGH SCHOOLS IN BENGKULU - Safnil Arsyad (EduLite: Journal of English Education, Literature and Culture, 2018)
It is widely accepted that the use of learning materials which accommodates students’ schemata is much more effective than the ones outside student’s present knowledge background. The objectives of this study are to describe the students’ learning style distribution and their perception on local oriented and learning style-based English learning materials in Bengkulu Province. The respondents were senior high school students in Bengkulu Province. The results show that : 1) the English learning materials can present a well-designed English learning materials for senior high schools students; 2) the English learning materials with picture stories and visual and audio learning media help students learn English; 3) the learning materials have been designed very well according to the students; 4) as reported by the students the strengths of the English learning materials is that it provides new information on tourism places in Bengkulu Province for the students, 5) the learning materials (the text books and VCD/CD) could improve their motivation to learn English. It can be concluded that local oriented and learning style-based learning materials can be not only more effective but also preferred by the students.